APOE ɛ4 allele and TOMM40‐APOC1 variants jointly contribute to survival to older ages. Issue 12 (3rd November 2022) - Kulminski, Alexander M.; Jain‐Washburn, Ethan; Philipp, Ian; He, Liang; Loika, Yury; Loiko, Elena; Bagley, Olivia; Ukraintseva, Svetlana; Yashin, Anatoliy; Arbeev, Konstantin; Stallard, Eric; Feitosa, Mary F.; et al.
Abstract: Age‐related diseases characteristic of post‐reproductive life, aging, and life span are the examples of polygenic non‐Mendelian traits with intricate genetic architectures. Polygenicity of these traits implies that multiple variants can impact their risks independently or jointly as combinations of specific variants. Here, we examined chances to live to older ages, 85 years and older, for carriers of compound genotypes comprised of combinations of genotypes of rs429358 ( APOE ɛ4 encoding polymorphism), rs2075650 ( TOMM40 ), and rs12721046 ( APOC1 ) polymorphisms using data from four human studies. The choice of these polymorphisms was motivated by our prior results showing that the ɛ4 carriers having minor alleles of the other two polymorphisms were at exceptionally high risk of Alzheimer's disease (AD), compared with non‐carriers of the minor alleles. Consistent with our prior findings for AD, we show here that the adverse effect of the ɛ4 allele on survival to older ages is significantly higher in carriers of minor alleles of rs2075650 and/or rs12721046 polymorphisms compared with their non‐carriers. The exclusion of AD cases made this effect stronger. Our results provide compelling evidence that AD does not mediate the associations of the same compound genotypes with chances to survive until older ages, indicating the existence of genetically heterogeneous mechanisms. The survival chances can be mainly associated with lipid‐ and immunity‐related mechanisms, whereas the AD risk, can be driven by the AD‐biomarker‐related mechanism, among others. Targeting heterogeneous polygenic profiles of individuals at high risks of complex traits is promising for the translation of genetic discoveries to health care. Abstract : The APOE ɛ4 allele and minor alleles of rs2075650 TOMM40 and rs12721046 APOC1 variants confer a higher risk of Alzheimer's disease compared with the ɛ4 allele and no minor alleles of these two polymorphisms. Here, we show that the same relationship characterizes chances to live 85 years and older. Nevertheless, we show that Alzheimer's disease does not mediate the associations of the same compound genotypes with chances to survive to 85+ years, indicating the existence of genetically heterogeneous mechanisms.